Astragaloside IV improves the pharmacokinetics of febuxostat in rats with hyperuricemic nephropathy by regulating urea metabolism in gut microbiota - Zhao, Zhen Xiong; Tang, Xiao Hui; Jiang, Sheng Lu; Pang, Jia Qian; Xu, Yu Bin; Yuan, Dan Dan; Zhang, Ling Ling; Liu, Hui Min; Fan, Qing (Frontiers in Pharmacology, 2022)
Hyperuricemic nephropathy (HN) is a common clinical complication of hyperuricemia. The pathogenesis of HN is directly related to urea metabolism in the gut microbiota. Febuxostat, a potent xanthine oxidase inhibitor, is the first-line drug used for the treatment of hyperuricemia. However, there have been few studies on the pharmacokinetics of febuxostat in HN animal models or in patients. In this study, a high-purine diet-induced HN rat model was established. The pharmacokinetics of febuxostat in HN rats was evaluated using LC-MS/MS. Astragaloside IV (AST) was used to correct the abnormal pharmacokinetics of febuxostat. Gut microbiota diversity analysis was used to evaluate the effect of AST on gut microbiota. The results showed that the delayed elimination of febuxostat caused drug accumulation after multiple administrations. Oral but not i.p. AST improved the pharmacokinetics of febuxostat in HN rats. The mechanistic study showed that AST could regulate urea metabolism in faeces and attenuate urea-ammonia liver-intestine circulation. Urease-related genera, including Eubacterium, Parabacteroides, Ruminococcus, and Clostridia, decreased after AST prevention. In addition, the decrease in pathogenic genera and increase in short-chain fatty acids (SCFA) producing genera also contribute to renal function recovery. In summary, AST improved the pharmacokinetics of febuxostat in HN rats by comprehensive regulation of the gut microbiota, including urea metabolism, anti-calcification, and short-chain fatty acid generation. These results imply that febuxostat might accumulate in HN patients, and AST could reverse the accumulation through gut microbiota regulation.